Z powrotem do oikos nomos, z powrotem do rzeczywistości… Materialistyczna transformacja kultury Zachodu a zwrot społeczno-kulturowy w ekonomii - Michalski, Michał A. (Człowiek i Społeczeństwo, 2018)
Michał A. Michalski, Z powrotem do oikos nomos, z powrotem do rzeczywistości… Materialistyczna transformacja kultury Zachodu a zwrot społeczno-kulturowy w ekonomii [Back to oikos nomos, Back to Reality… Materialistic Transformation of the Western Culture and Socio-Cultural Turn in Economics] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 203–215, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. In this article, I put forward the thesis that the current socio-economic situation is to a large extent caused by the changes that have taken place in Western culture over the last few centuries. This means that, to a large extent, the considerations discussed here refer to the perspective of economic culture. The reason for undertaking this issue is paradoxical situation of socio-economic stagnation and recourse in the contemporary West which has achieved unprecedented level of social, scientific and technological development. In order to explain this problem, the article proposes to analyse the process of materialisation of the Western culture which means that the materialistic point of view colonizes at the same time capitalist and socialist concepts and policies. It becomes evident e.g. in the prioritizing economic policy and economic development as the universal solution to all social challenges and marginalizing metaphysical aspects of human and social existence. According to the conclusion of the article it is necessary to understand the influence of materialistic point of view in order to rethink and analyse contemporary shape of Western culture and condition of Western civilization.